Women’s Social Autonomy in QS. At-Taubah [9]:71: A Comparative Study of Classical and Contemporary Qur’anic Exegesis - Jannah, Rieka Raudhatul; Falah, Mega Satria Nurul (TAFSE: Journal of Qur'anic Studies, 2025)
This study examines the concept of women’s social autonomy in QS. At-Taubah [9]:71 through a comparative analysis of classical and contemporary Qur’anic exegesis. The verse establishes a framework of mutual responsibility between believing men and women through the concept of wilāyah and the shared obligation of amr ma‘rūf wa nahy munkar. This study employs a qualitative library-based approach grounded in thematic interpretation and comparative-interpretative analysis. The analysis focuses on selected classical exegetes, including al-Ṭabarī, Ibn Kathīr, and al-Qurṭubī, alongside contemporary interpretations by M. Quraish Shihab and Nasaruddin Umar. The findings show that classical tafsir consistently affirms the equality of moral and spiritual responsibility between men and women, although it does not extensively elaborate the social implications of this principle. Contemporary interpretations build on this foundation by articulating wilāyah as a non-hierarchical relational concept that supports women’s participation in social and religious life. The comparison indicates continuity in core ethical principles alongside a shift in interpretive emphasis toward social engagement. This study proposes a conceptual formulation of women’s social autonomy derived from the internal structure of the verse, integrating theological, social, and ethical dimensions. The analysis demonstrates that women’s social autonomy is grounded in Qur’anic ethics rather than external constructs, and provides a framework for understanding women’s participation in contemporary Muslim societies, particularly in Indonesia. The study contributes to Qur’anic studies by offering a systematic conceptualization of social autonomy based on comparative tafsir and by highlighting the relevance of Qur’anic ethical principles for ongoing discussions of gender and social responsibility.